Design, Development, and Deployment of Archival Information Management System (Aims)tFor the Local Civil Registry of Lasam, Cagayan - Brunio, Princess Dianne; Javier, Billy (Studies in Technology and Education, 2026)
Civil registration is essential for establishing legal identity and ensuring access to public services; however, many local civil registry offices, particularly in rural areas, continue to rely on manual, paper-based systems, resulting in inefficiencies, delays in service delivery, difficulty in record retrieval, and increased risk of data loss or damage. This study addressed these challenges by developing an Archival Information Management System (AIMS) tailored to the operational needs of the Local Civil Registry of Lasam, Cagayan. The study aimed to determine how a digital archival system could improve the efficiency, accuracy, and accessibility of civil registry records. Using a descriptive-analytical research design and developmental approach, data were gathered through interviews, observations, and document analysis. The system was developed using the Agile Software Development Model under the System Development Life Cycle (SDLC) and evaluated using ISO 25010:2023 standards and the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2). Results revealed that AIMS significantly improved record management through faster data encoding, efficient storage, and quick retrieval of records, demonstrating very high quality and high user acceptance. The study concludes that AIMS enhances operational efficiency and public service delivery and is recommended for adoption in other local government units.